THE ARCHETYPE OF DEATH IN SLAVIC MYTHOLOGY AS PORTRAYED IN TEA OBREHT'S THE TIGER'S WIFE - RENALDO PANGESTU SOEHARTO, 121411233014 (2019)
This study aims to find the representation of bad death from Slavic belief on death in the novel The Tiger’s Wife written by Tea Obreht. This study is a qualitative research which applies from Carl Gustav Jung’s concept of collective unconscious which expanded into mythological criticism because collective unconscious creates people beliefs or the archetype. The Tiger’s Wife represented the death from the Slavic belief in the cause of death on the dominant characters. The cause of death or dying, made people act strangely and try to do what they want to do in their limited time of life, however, people died coincidently and the cause of it stated as unnatural because people do not expect that someone will be died in that way. None of the previous studies on The Tiger’s Wife set their aim to find the representation of the death that occurred in the novel.